PRINSIP KEPASTIAN HUKUM PEMBERHENTIAN NOTARIS AKIBAT DINYATAKAN PAILIT - Amira Inaz Clarissa Pambudi; Fanny Tanuwijaya; Fendi Setyawan (Universitas Islam Darul Ulum, 2022)
Notaries basically work to get fair and proper compensation and treatment in an employment relationship, so a notary should be able to re-apply as a notary after completing the bankruptcy process. Because the notary who has been declared bankrupt and has been dismissed by the minister has paid compensation to the creditor, so that the creditor has received his rights. The UUJN provides provisions if a notary who has been declared bankrupt will be dishonorably dismissed from his position as regulated in Article 12 letter a of the UUJN. The type of research used is normative juridical, with a statutory approach and a conceptual approach as well as a historical approach. The regulation of the bankruptcy notary in Article 9 and Article 12 of UUJN is vague, ambiguous and inconsistent. A Notary as a General Officer is given the authority to make an authentic deed. Future arrangements regarding the reappointment of notaries who have completed the bankruptcy process, that there needs to be complete and specific regulations, because there is a void in norms regarding the reappointment of notaries who have completed the bankruptcy process.